PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN BERBASIS SPARKOL VIDEOSCRIBE UNTUK PARA GURU DI SEKOLAH MENENGAH PERTAMA MUHAMMADIYAH KOTABUMI LAMPUNG UTARA - Rulik Setiani; Nur Mei Ningsih; Asep Hardiyanto; Khusnul Khotimah (Universitas Majalengka, 2023)
The main problem in this Community Service activity is the lack of motivation and movement of teachers in the school in presenting information technology-based materials that can support the distance learning process during a pandemic. As a result, students become less enthusiastic and less motivated to take part in learning because the teacher only gives assignments without any explanation so that students have difficulty doing them. Teachers should be able to use various learning media to convey material so that learning can be carried out smoothly. Weaknesses of SMP Muhammadiyah Kotabumi that the teachers lack updates regarding digital learning media so that in carrying out learning it is less attractive to students. From the problems described above, the community service team provides a solution to the problem by carrying out assistance in making interactive learning media based on the Sparkol Videoscribe application for teachers at SMP Muhammadiyah Kotabumi North Lampung. The purpose of this activity is to improve the skills of teachers in making sparkol videoscribe-based digital learning media, and it is hoped that the teachers will have skills in making digital learning media so that the distance learning process can be carried out properly.